Some mechanical properties of plywood produced from eucalyptus, beech, and poplar veneer - Cihad Bal, Bekir; Bektaş, İbrahim (Maderas. Ciencia y Tecnología, 2025)
In this study, we determined the flexural properties and tensile shear strength of five-ply plywood panels produced with eucalyptus (Eucalyptus grandis), beech (Fagus orientalis), and hybrid poplar (Populus x euramericana) using urea-formaldehyde (UF), melamine-urea-formaldehyde (MUF) and phenol-formaldehyde (PF) adhesives. Flexural properties were tested on both parallel and perpendicular to grain samples. Tensile shear-strength tests were conducted on four glue lines of the plywood panels, and the effects of species of trees, type of adhesives, and direction of load were determined. The results of variance analyses showed that the effects of species of trees, direction of load, and type of adhesive on flexural properties were significant, but it was determined by specific flexural properties that the effect of the type of adhesive was based on the density of the plywood. In addition, as a result of findings, it can be said that specific mechanical properties may be a good predictor for comparative studies.